Evaluation of an Integrated Amphiphilic Surfactant as an Alternative to Traditional Polyvinylpyrrolidone Coatings for Hydrophilic Intermittent Urinary Catheters. (December 2022) - Pollard, David; Allen, Daniel; Irwin, Nicola J.; Moore, Jessica V.; McClelland, Nicola; McCoy, Colin P.
Abstract: Introduction: Polyvinylpyrrolidone (PVP) is commonly used to provide catheters with a lubricious coating when hydrated, however, it becomes adhesive as it dries which may cause catheters to adhere to the urethral mucosa and potentially leave a sticky residue. The aim of this study was to compare catheters coated with PVP with an integrated amphiphilic surfactant (IAS) using an in vitro agar model to assess potential sticking and shedding of the catheter surface on removal. Methods: Hydrated catheter samples were attached to the upper grips of a texture analyser, lowered vertically into agar, and withdrawn after two minutes. Resultant force-distance plots were used to determine maximum forces for withdrawal. Catheter surfaces were stained with red dye and the agar was visually inspected for dye residues after withdrawal. Results: A sharp peak in force on initial withdrawal was observed for six of the eight PVP-containing catheters indicating that a greater force was required to initiate withdrawal from the agar suggesting sticking of the catheter. This peak was absent for catheters with the IAS which also displayed lower mean maximum withdrawal forces compared with many of the PVP-based catheters ( p < 0.05). Red dye was observed to remain in the agar after withdrawal of all PVP-coated catheters indicating that there had been shedding of the hydrophilic coating. In contrast, there was no evidence of dye residues in the agar from IAS-based catheters suggesting that no shedding occurred. Conclusion: IAS catheters show absence of adhesive properties and delamination observed for many PVP catheters when tested in vitro . Highlights: Friction during intermittent catheterisation increases risks of trauma to the urethra. PVP on catheters becomes adhesive as it dries which may cause catheters to adhere. Catheters with an integrated amphiphilic surfactant show absence of sticking.